Religiousness Associated with Type 2 Diabetes Care Management: A Concept Analysis - Anita Sukarno; Rian Adi Pamungkas (Alta Dharma Publisher, 2020)
The concept of religiousness role on the type 2 diabetes care management has not clearly explained. Terminology of “religiousness” and “spirituality” are sometimes confused and broadly explained. We applied Walker and Avant’s concept analysis model to explore the meaning of religiousness on diabetes management among type 2 diabetes patients through selecting a concept, determining the analysis purpose, identifying a model case, investigating attributes, antecedents, and consequences, as well as defining empirical referents. The findings identified attributes of religiousness role in diabetes care management context including religious belief, religious practice, religious support, and religious coping. Antecedents included age, gender, education, race or ethnicity, religions, income, employment. Glycemic control and psychological well-being were documented as consequences. Health care provider might consider the antecedent as or inhibitor factors to impede the expected outcome. Further research might need to take religiousness role into account to type 2 diabetes care management intervention